PERKAWINAN POLIGAMI DALAM PERSPEKTIF HUKUM ISLAM - Arsyad Said (Maleo Law Journal, 2017)
Islam is a perfect religion, humanitarian problems are explained mentally, responded through a religious shari'ah called polygamy, which in a simple sense means having more than one wife. Islam has justified a husband for polygamy if he has met the criteria specified. However, the implementation of polygamy is not without obstacles, challenges or risks that exist. The reaction of some Muslims who respond negatively to the practice of polygamy has required a psychological phenomenon that occurs primarily for people who practice polygamy. Excessive reaction shown by some Muslims through various media has made this polygamy as if something bad is even forbidden to do.Keywords : Mariage, Polygamy, Islamic Law